Pengaruh Pemanfaatan Museum Sebagai Sumber Belajar Terhadap Hasil Belajar Siswa Pada Materi Pakaian Adat Tradisional Bengkulu Di SD Negeri 5 Kota Bengkulu - Eka Purnama Sari; Sri Dadi; Syahril Yusuf (Universitas Bengkulu, 2018)
This study aims to determine the effect of the use of the museum as asource of learning on student learning outcomes on traditional clothingmaterials Bengkulu class IV SD Negeri 5 Bengkulu City. The type ofresearch is quantitative, using quasi-experimental methods with thedesign of The Matching Only Pretest-Posttest Control Group Design. Thepopulation in this study is the fourth grade students of SD Negeri 5 KotaBengkulu. The sample in this study were students of class IVA whichamounted to 34 students as experimental class and IVB which amountedto 34 students as control class. Sampling using Cluster RandomSampling technique.Research instrument in the form of learning resulttest. Based on the results of the hypothesis by using t-test at a significantlevel of 5% obtained tcount 3.48> ttable 2.00. Thus it can be concluded,that there is influence of the use of the museum as a source of learning onstudent learning outcomes on traditional clothing material Bengkulu inclass IV SD Negeri 5 Bengkulu City.